2019
DOI: 10.3389/fneur.2019.00860
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subcortical Infarcts Cause Secondary Degeneration in the Remote Non-involved Cortex and Connecting Fiber Tracts

Abstract: Background and Purpose: Remote white matter and cortex reorganization may contribute to functional reorganization and clinical outcome after acute infarcts. To determine the microstructural changes in the remote intact corticospinal tract (CST) and precentral gyrus cortex connected to the acute infarct after subcortical stroke involving the CST over 6 months. Methods: Twenty-two patients with subcortical stroke involving the CST underwent magnetic resonance imaging (MRI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Similar to the previous study, infarcts cause motor area focal thinning in remote cortex via degeneration of inter-hemispheric connection ber of the corpus callosum [36,37], we found a change in the connection between the frontal hemispheres, and a small area in contralesional frontal cortex decreased in FA value. It has been reported that secondary degeneration occurred in the ipsilesional precentral gyrus after subcortical stroke involving the CST at the 6-month follow-up in stroke patients by calculating the mean kurtosis (MK) value of manually drawing ROI from Diffusion kurtosis imaging (DKI) imaging study [38]. Now we speculate the degeneration in remote parts of CST occurred in acute and subacute phases of stroke.…”
Section: The Bilateral Frontal Lobementioning
confidence: 72%
See 1 more Smart Citation
“…Similar to the previous study, infarcts cause motor area focal thinning in remote cortex via degeneration of inter-hemispheric connection ber of the corpus callosum [36,37], we found a change in the connection between the frontal hemispheres, and a small area in contralesional frontal cortex decreased in FA value. It has been reported that secondary degeneration occurred in the ipsilesional precentral gyrus after subcortical stroke involving the CST at the 6-month follow-up in stroke patients by calculating the mean kurtosis (MK) value of manually drawing ROI from Diffusion kurtosis imaging (DKI) imaging study [38]. Now we speculate the degeneration in remote parts of CST occurred in acute and subacute phases of stroke.…”
Section: The Bilateral Frontal Lobementioning
confidence: 72%
“…The connections between the cerebrum and the cerebellum pass through the cerebral peduncle in brainstem, so we assume that the weakening of connections to the cerebellum is partially consistent with the decrease in FA in brainstem. Previous DTI studies also found a decrease in FA in midbrain after stroke by manually plotting ROI [38]. A recent study found the role of the cerebellum for residual motor output by facilitating cortical excitability in chronic stroke [45].…”
Section: Cerebellummentioning
confidence: 87%
“…So we assume that the weakening of those connections is partially consistent with the decrease in FA in the brainstem. Previous DTI studies also found decreased FA in midbrain of the stroke patients by manually plotting ROI [38]. A recent study indicated that the cerebellum plays a role on residual motor output by facilitating cortical excitability in chronic stroke [45].…”
Section: The Cerebellummentioning
confidence: 86%
“…Similar to previous studies results showing infarct-related focal thinning of the motor area in remote cortex via degeneration of inter-hemispheric connection ber of the corpus callosum [36,37], we found changes in the connection between the frontal hemispheres, as well as reduced FA values in a small area located in the contralesional frontal cortex. It has been reported that secondary degeneration occurred in the ipsilesional precentral gyrus after subcortical stroke involving the CST at the 6-month follow-up in stroke patients by calculating the mean kurtosis (MK) value of manually drawing ROI from diffusion kurtosis imaging (DKI) imaging study [38]. We speculated that the degeneration in remote parts of the CST occurred in subacute phases of stroke.…”
Section: The Bilateral Frontal Lobementioning
confidence: 99%
“…Indeed, both clinical studies on stroke patients and animal studies with stroke models reveal the critical role of infarct volume on functional outcome ( Peeling et al, 2001 ; Roof et al, 2001 ; Zaidi et al, 2012 ; Vagal et al, 2015 ; Turner et al, 2016 ). In addition, accumulating clinical evidence has shown that delayed secondary degeneration also occurs in remote non-ischemic cortical regions ( Duering et al, 2015 ; Wei et al, 2019 ). Axonal connectedness is believed to be the key linking remote neuronal damage to the primary lesion site ( Dikranian et al, 2008 ), suggesting that potential white matter (WM) degeneration also occurs after stroke.…”
Section: Introductionmentioning
confidence: 99%